1995
DOI: 10.1091/mbc.6.7.841
|View full text |Cite
|
Sign up to set email alerts
|

Induction of carcinoma cell migration on vitronectin by NF-kappa B-dependent gene expression.

Abstract: Integrin avf35 promotes FG carcinoma cell adhesion to vitronectin yet requires protein kinase C (PKC) activation for migration on this ligand. Here we report that this PKCdependent cell motility event requires NF-KB-dependent transcription. Specifically, a component within nuclear extracts prepared from PKC-stimulated FG cells exhibited a significant increase in binding activity to a synthetic oligonucleotide containing a consensus KB sequence. These nuclear DNA-binding complexes were shown to be comprised of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 55 publications
3
54
0
1
Order By: Relevance
“…Although other groups have suggested that NF-kB is involved in the migration of pancreatic carcinoma or keratinocytes (Yebra et al, 1995;Benoliel et al, 1997), these previous studies provide little insight into events responsible for NF-kB induction. More importantly, our data indicated a significant increase in transcription of b1 integrin mRNA following the CIV treatment.…”
Section: Sn-50m 50µg/mlmentioning
confidence: 96%
See 1 more Smart Citation
“…Although other groups have suggested that NF-kB is involved in the migration of pancreatic carcinoma or keratinocytes (Yebra et al, 1995;Benoliel et al, 1997), these previous studies provide little insight into events responsible for NF-kB induction. More importantly, our data indicated a significant increase in transcription of b1 integrin mRNA following the CIV treatment.…”
Section: Sn-50m 50µg/mlmentioning
confidence: 96%
“…Recently, NF-kB has been shown to be required for cell migration mediated by some ECM proteins. For example, NF-kB was necessary for the migration of a pancreatic cell line in response to vitronectin, as well as the chemotaxis of keratinocytes in response to insulin (Yebra et al, 1995;Benoliel et al, 1997). Whether b1 integrindependent tumor cell migration requires the induction of transcription factors, including NF-kB, needs further elucidation.…”
Section: Introductionmentioning
confidence: 99%
“…PKC activity is involved in integrin-mediated responses including adhesion, motility and membrane ru ing (Lewis et al, 1996;Klemke et al, 1994;Yebra et al, 1995;Miyata et al, 1989). It can also a ect invasive behavior (Ways et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The integrin family of cell adhesion receptors mediates cell attachment to extracellular matrix proteins and is known to play a critical role in cell motility (12)(13)(14)(15), thus contributing to a variety of biological processes including angiogenesis, wound healing, and tumor cell invasion and metastasis (16 -18).…”
mentioning
confidence: 99%